The biliary epithelium gives rise to liver progenitor cells. Issue 4 (21st August 2014) - Rodrigo‐Torres, Daniel; Affò, Silvia; Coll, Mar; Morales‐Ibanez, Oriol; Millán, Cristina; Blaya, Delia; Alvarez‐Guaita, Anna; Rentero, Carles; Lozano, Juan José; Maestro, Miguel Angel; Solar, Myriam; Arroyo, Vicente; et al.
<x xml:space="preserve">Abstract</x> Severe liver diseases are characterized by expansion of liver progenitor cells (LPC), which correlates with disease severity. However, the origin and role of LPC in liver physiology and in hepatic injury remains a contentious topic. We found that ductular reaction cells in human cirrhotic livers express hepatocyte nuclear factor 1 homeobox B (HNF1β). However, HNF1β expression was not present in newly generated epithelial cell adhesion molecule (EpCAM)‐positive hepatocytes. In order to investigate the role of HNF1β‐expressing cells we used a tamoxifen‐inducible Hnf1βCreER/R26RYfp/LacZ mouse to lineage‐trace Hnf1β+ biliary duct cells and to assess their contribution to LPC expansion and hepatocyte generation. Lineage tracing demonstrated no contribution of HNF1β+ cells to hepatocytes during liver homeostasis in healthy mice or after loss of liver mass. After acute acetaminophen or carbon tetrachloride injury no contribution of HNF1β+ cells to hepatocyte was detected. We next assessed the contribution of Hnf1β+‐derived cells following two liver injury models with LPC expansion, a diethoxycarbonyl‐1, 4‐dihydro‐collidin (DDC)‐diet and a choline‐deficient ethionine‐supplemented (CDE)‐diet. The contribution of Hnf1β+ cells to liver regeneration was dependent on the liver injury model. While no contribution was observed after DDC‐diet treatment, mice fed with a CDE‐diet showed a small population of hepatocytes derived from Hnf1β+ cells that were expanded to 1.86% of total hepatocytes after injury recovery. Genome‐wide expression profile of Hnf1β+‐derived cells from the DDC and CDE models indicated that no contribution of LPC to hepatocytes was associated with LPC expression of genes related to telomere maintenance, inflammation, and chemokine signaling pathways. Conclusion: HNF1β+ biliary duct cells are the origin of LPC. HNF1β+ cells do not contribute to hepatocyte turnover in the healthy liver, but after certain liver injury, they can differentiate to hepatocytes contributing to liver regeneration. (Hepatology 2014;60:1367–1377)